Manajemen Asuhan Kebidanan Antenatal Care Patologi Pada Ny “K” Dengan Hiperemesis Gravidarum Tingkat I Gestasi 12 minggu 2 Hari Di RS Al-Jala Ammari Makassar Tanggal 03 Agustus – 21 Agustus 2022 : Midwifery Care Management of Antenatal Care Pathology in Mrs. “K” with Hyperemesis Gravidarum Level I in the Gestational Period of 12-14 Weeks at Al-Jala Ammari Hospital of Makassar, August 3rd - August 21st 2022 - Nurhidayanti; Sitti Saleha; Zelna Yuni Andryani (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2023)
Introduction Hyperemesis Gravidarum is a complication in pregnancy characterized by excessive nausea and vomiting which can affect the general condition of pregnant women. Hyperemesis Gravidarum is divided into three levels, namely level I (mild), level II (moderate), level III (severe). The purpose of this study was to provide Antenatal Care Midwifery Care for Mrs. “K” with the case of Hyperemesis Gravidarum Level I in the gestational period of 12-14 weeks at Al-Jala Ammari Hospital of Makassar. Method The study was conducted by utilizing a 7-stage of Varney management approach. Result of this study indicated that during the caring management, various observations and four home visits were conducted. After the treaments, the condition of the patient gradually improved. This is evidenced by the results of the last observation at the patient’s house showing that her vital signs were within normal, and her excessive nausea and vomiting were resolved. Moreover, the patient’s appetite had also considerably improved. Conclusion The hyperemesis gravidarum experieced by the patient could be well handled and treated. The treatments were given both during the home visits and in the hospital.